104k views
0 votes
I need help asap

Which equation represents a circle with diameter endpoints at (−3,−2) and (1,−4)?


A

(x−1)2+(y−3)2=20


B

(x+1)2+(y+3)2=5


C

(x+1)2+(y+3)2=20


D

(x−1)2+(y−3)2=5

User MMMTroy
by
5.0k points

1 Answer

4 votes

Option C:
(x+1)^2+(y+3)^2=20 is the equation of the circle.

Step-by-step explanation:

Given that the endpoints of the circle are at (-3,-2) and (1,-4)

The equation of the circle can be determined using the formula,


(x-a)^(2)+(y-b)^(2)=r^(2)

where
(a, b) are the coordinates of the center and r is the radius.

Center:

The center of the circle can be determined using the midpoint formula,


Center=((x_1+x_2)/(2), (y_1+y_2)/(2) )

Substituting the coordinates (-3,-2) and (1,-4) in the above formula, we get,


Center=((-3+1)/(2), (-2-4)/(2) )


Center=((-2)/(2), (-6)/(2) )


Center=(-1,-3 )

Thus, the center of the circle is at (-1,-3)

Radius:

The radius of the circle can be determined using the distance formula,


r=\sqrt{\left(x_(2)-x_(1)\right)^(2)+\left(y_(2)-y_(1)\right)^(2)}

Substituting the coordinates (-3,-2) and (1,-4) in the above formula, we get,


r=\sqrt{\left(1+3\right)^(2)+\left(-4+2\right)^(2)}


r=\sqrt{\left(4\right)^(2)+\left(-2\right)^(2)}


r=√(\left16+\left4)


r=√(20)

Thus, the radius of the circle is
√(20)

Equation of the circle:

Substituting the center and the radius of the circle in the equation
(x-a)^(2)+(y-b)^(2)=r^(2), we get,


(x+1)^2+(y+3)^2=(√(20) )^2

Simplifying, we get,


(x+1)^2+(y+3)^2=20

Therefore, the equation of the circle is
(x+1)^2+(y+3)^2=20

Hence, Option C is the correct answer.

User Pradeep Nooney
by
5.1k points